Analisis Perbandingan Ipal Lama Dan Ipal Baru Pada Rumah Sakit Telogorejo Semarang - Wardani, Annisa Rizki Yudiya; Kiswari, Kutin Beta; Mukhlisin, Muhammad; Suwanto, Bodja (Politeknik Negeri Semarang, 2014)
Hospital is a health care institution which becomes educational place of research and health workers. On the other side, hospital often potentially causes environmental pollution due to its liquid waste. It is said in Law no 20 year 1990 that ?setiap orang atau badan yang membuang limbah cair wajib mentaati baku mutu limbah cair sebagaimana ditentukan dalm izin pembuangan limbah cair yang ditetapkan baginya?. Therefore, it is necessary to create sewage treatment plant system or STP to manage liquid waste. The system is quite good until encounters overloading. But now, Telogorejo Hospital has upgraded its STP into the newest STP with higher capacity of water treatment. Objectives of this research are to analyze the effectiveness of operational system and procedure of IPAL and also compare the previous IPAL with the newest one on the Telogorejo Hospital. Research method used in this research are interview, observasion, secondary data collecting, and data analyzing. The result shows that the upgrading of the IPAL, from capacity, process and effluent quality, is much more effective.